Luminal Narrowing Alone Allows an Accurate Diagnosis of Crohn's Disease Small Bowel Strictures at Cross-Sectional Imaging. (15th December 2020) - Stocker, Daniel; King, Michael J; El Homsi, Maria; Carbonell, Guillermo; Bane, Octavia; Cuevas, Jordan; Liu, Qingqing; Cho, Judy; Doucette, John T; Greenstein, Alexander J; Colombel, Jean-Frederic; Harpaz, Noam; et al.
Abstract: Background and Aims: Current consensus recommendations define small bowel strictures [SBS] in Crohn's disease [CD] on imaging as luminal narrowing with unequivocal upstream bowel dilation. The aim of this study was to [1] evaluate the performance of cross-sectional imaging for SBS diagnosis in CD using luminal narrowing with upstream SB dilation and luminal narrowing with or without upstream dilation, and [2] compare the diagnostic performance of computed tomography [CT] and magnetic resonance enterography [MRE] for SBS diagnosis. Methods: In total, 111 CD patients [81 with pathologically confirmed SBS, 30 controls] who underwent CT and/or MRE were assessed. Two radiologists [R1, R2] blinded to pathology findings independently assessed the presence of luminal narrowing and upstream SB dilation. Statistical analysis was performed for [1] luminal narrowing with or without SB upstream dilation ['possible SBS'], and [2] luminal narrowing with upstream SB dilation ≥3 cm ['definite SBS']. Results: Sensitivity for detecting SBS was significantly higher using 'possible SBS' [R1, 82.1%; R2, 77.9%] compared to 'definite SBS' [R1, 62.1%; R2, 65.3%; p < 0.0001] with equivalent specificity [R1, 96.7%; R2, 93.3%; p > 0.9]. Using the criterion 'possible SBS', sensitivity/specificity were equivalent between CT [R1, 87.3%/93.3%; R2, 83.6%/86.7%] and MRE [R1, 75.0%/100%; R2: 70.0%/100%]. Using the criterion 'definite SBS', CT showed significantly higher sensitivity [78.2%] compared to MRE [40.0%] for R1 but not R2 with similar specificities [CT, 86.7–93.3%; MRE, 100%]. Conclusion: SBS can be diagnosed using luminal narrowing alone without the need for upstream dilation. CT and MRE show similar diagnostic performance for SBS diagnosis using luminal narrowing with or without upstream dilation.